A Long Term Study on Characterization and Source Apportionment of Particulate Pollution in Klang Valley, Kuala Lumpur - Shamsiah, Abdul Rahman; Mohd Suhaimi, Hamzah; Md Suhaimi, Elias; Nazaratul Ashifa, Abdullah Salim; Azian, Hashim; Shakirah, Shukor; Wee, Boon Siong; Abdul Khalik, Wood (Taiwan Association for Aerosol Research, 2015)
Samples of airborne particulate matter, PM2.5 and PM10–2.5 were collected using a Gent stacked filter sampler at an urban site, Klang Valley, Kuala Lumpur between January 2002–December 2011. The samples were analyzed for their elemental composition and black carbon content by Particle Induced X-ray Emission (PIXE) and light absorption, respectively. The annual average for PM2.5, PM10–2.5 and PM10 ranged from 21 to 35, 18 to 26 and 44 to 56 μg m–3, respectively. Factor analysis method and the Positive Matrix Factorisation (EPA PMF3) technique were also applied to the fine fraction data set in order to identify the possible sources of particulate matter and their contributions to the ambient particulate matter concentrations in the Klang Valley. A five factor PMF solution was found for PM2.5 particulate matter. The sources identified were; motor vehicles, industry, smoke/biomass burning, secondary sulphate and soil. It was found that the primary source of haze air particulate matter was locally generated mostly from vehicular emissions which contribute about 35% of the PM2.5 mass. The Hybrid Single Particle Lagrangian Intergrated Trajectory (HYSPLT) model was also used to explore possible long range transport of pollution. Smoke trans-boundary events were identified based on fine potassium from the data base in 2004, 2006 and 2008.